古代漢語 副詞의 범주 재 고찰 - 정성임; Jung Sung Yim (중국연구, 2017)
The method of the study in this research paper is consistent with < The ancient Chinese language sentence composition and phrase research (1) - The adverb of adverbial phrase is a lord with non- adverb of adverbial phrase - >. The category of adverb which is based on ≪SHIJI[史記]≫ has been re-examined with the broader point of view using reference from Xianqin[先秦]-Lianghan[兩漢]. The following adverbs are from the category based on Xianqin[先秦]-Lianghan[兩漢]. Degree adverb: 尤, 頗, 更 etc. Range/Mutual adverb: 只, 咸, 皆, 悉, 但, 徒, 祗(?), 直, 僅, ?, 唯, 相, 互, 俱 etc. Time/Frequency adverb: 已, 旣, 將, 方, 輒, 暫, 又, 嘗, 亦, 常, 卽, 剛, 頓, 乍 etc. Stationary/Speculation adverb: 固, 必, 寧(차라리), 庶, 幾, 蓋, 殆, 尙, 猶 etc. Negation/Response adverb: 未, 否, 不, 弗, 非(匪), 唯(惟·維) etc. Cross-questioning adverb: 豈, 寧(어찌), 庸 etc. Relative adverb: 乃, 則(卽), 却(却), 且, 才(?) etc. Conversion adverb: 雖, 縱 etc.